2021
DOI: 10.1097/spv.0000000000001108
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Early Cyclosporine Treatment for Hunner Lesion Interstitial Cystitis

Abstract: Hunner lesion interstitial cystitis (HLIC) is a form of interstitial cystitis/bladder pain syndrome (IC/BPS), occurring in 5%-57% of patients. HLIC is diagnosed by the presence of Hunner lesions on cystoscopy. Cyclosporin A (CyA) is an immunosuppressant that inhibits cytokine interleukin 2 transcription. Previous studies have shown that CyA is effective in the treatment of IC, but the 22Obstetrical and Gynecological Survey

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…13,15 A strength of our study was the prospective long-term follow-up which allowed for rigorous monitoring of CyA efficacy as well as systematic control of blood pressure and creatinine values. While some studies reported creatinine variation over a few months only, 15,23 our study reinforced the safety of a prolonged CyA usage which is crucial considering that long-term treatment might be necessary to maintain relief. Moreover, there were no loss at follow-up and recall bias was avoided by conducting a longitudinal prospective follow-up.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…13,15 A strength of our study was the prospective long-term follow-up which allowed for rigorous monitoring of CyA efficacy as well as systematic control of blood pressure and creatinine values. While some studies reported creatinine variation over a few months only, 15,23 our study reinforced the safety of a prolonged CyA usage which is crucial considering that long-term treatment might be necessary to maintain relief. Moreover, there were no loss at follow-up and recall bias was avoided by conducting a longitudinal prospective follow-up.…”
Section: Discussionsupporting
confidence: 63%
“…Previous IC/BPS studies have reported hypertension and nephrotoxicity as the main adverse events with daily CyA doses of 2 or 3 mg/kg. [13][14][15] Recently, Vollstedt et al 23 reported that 24% of their cohort, receiving a fixed dose of 100 mg daily as maintenance treatment, experienced new or worsening in hypertension. This adverse event was reported in only 14% of our cohort, which may perhaps be explained by the dosage based on weight and the effort to taper down the dose (median daily dose of 80 mg).…”
Section: Discussionmentioning
confidence: 99%
“…GRO-KC elevation is consistent with the in ltration of neutrophils being a hallmark of acute in ammation and not chronic in ammation which typically de nes IC/BPS. However, acute in ammation is critical in the are up of symptoms in IC/BPS patients and therefore elevation of urinary GRO/KC may foreshadow the advent of acute in ammation that can be targeted with non-steroidal anti-in ammatory drugs to prevent the worsening of symptoms and avoid aggressive treatment with steroids and immune suppressants for the are up of IC/BPS (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the presence of intense chronic inflammation in the HIC bladder, prior studies examined the utility of immunomodulatory therapies for patients with HIC; these include cyclosporine A or corticosteroids. To date, cyclosporine A has been the most frequent treatment for HIC, and it improves pain and urinary symptoms in refractory patients significantly [14] , [15] , [16] , [24] , [25] , [26] . However, the drug is associated with significant adverse events such as elevated serum creatinine levels, gingival hyperplasia, hypertension, and susceptibility to lymphoproliferative malignancies and skin malignancies [14] , [15] , [24] , [25] .…”
Section: Discussionmentioning
confidence: 99%